Zbiory informacji na potrzeby zarządzania w ochronie zdrowia - Hass-Symotiuk, Maria; Mućko, Przemysław; Jakimowicz, Hanna (Information Sets for Management Purposes in Health Care, 2008)
The article contains a detailed review and analysis of information sets prepared for management purposes in health care. Information needs of management are specified at three levels of administration, i.e. micro level, mezzo level, and macro level. These needs are satisfied through different reporting requirements set upon health care organizations. Information sets include financial information (about fixed and working assets, debts, revenues, costs, gains/looses) and non-financial, and are reported to several different bodies (Ministry of Health, founding bodies, payers, Central Statistical Office). In conclusion, the lack of coherence among different reporting systems in health care is highlighted.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 25-34